(untitled) (Research, Society and Development, 2021)
During the act of giving birth, the woman has several feelings, however, currently with the institutionalization of childbirth in hospitals, there is no prioritization of these emotions and physiological aspects, what exists is excessive processing. This can lead to a lack of personal contact and emotional aspects take a back seat. In this sense, the study aims to identify whether good practices in the delivery room, from the components of humanized childbirth, influence the anxiety score of women in the postpartum immediately. The study is prospective and cross-sectional, with 810 postpartum women, who signed the IC or TALE, from the deactivated groups in a philanthropic maternity hospital in Sergipe. The instruments used in the research were questionnaires based on two conceptions of anxiety. Thus, the factors found to influence anxiety were skin-to-skin contact, breastfeeding in the first hour postpartum, type of delivery, use of non-pharmacological practices for pain relief, expulsion position, presence of free choice companion and a non-violent birth.